A study on the role of sea ice in the nitrous oxide cycle in the Prydz Bay, Antarctica - Wu, Man; Zhan, Liyang; Liu, Jian; Zhang, Jiexia; Ye, Wangwang; Delille, Bruno (Frontiers in Marine Science, 2024)
N2O is one of the most important greenhouse gases and ozone depletor, which was a matter of more and more concerned. The Southern Ocean was considered as one of the most important N2O source and was believed to account for ~1/4 of oceanic budget.However, there is uncertainty about this budget due to limited data availability. In this study, field and lab works were conducted for better understanding of N2O dynamics during sea ice melting and sea ice formation. In the field study, taking advantage of the Chinese Antarctic cruise, a 10 days' time series study was carried out at a station in the Prydz Bay, Antarctica, where, surface water N2O was observed continuously, and the adjacent ice cores were taken for N2O analysis. In the lab, an ice growing simulation system was constructed to study the N2O dynamics during the sea ice formation. The result of endmember mixing models and calculation of N2O partition in three phases during sea ice formation provide important information about the dynamics of N2O during ice melting and sea ice formation processes, that is, the sea ice melting regulated N2O concentration and saturation status, which can be an explanation for reported N2O undersaturation observed in polar oceans, whereas during the sea ice formation, most of the N2O will be expelled to the deeper water while a small amount of retain the sea ice and less amount of N2O release to the atmosphere.